Chemokine Receptor and Ligand Upregulation in the Diaphragm during Endotoxemia and Pseudomonas Lung Infection - Alexandre Demoule; Maziar Divangahi; Linda Yahiaoui; Gawiyou Danialou; Dusanka Gvozdic; Basil J. Petrof (Mediators of Inflammation)
Sepsis-induced diaphragmatic inflammation has been associated with respiratory failure, but the role of chemokines in this process has not been evaluated. Here we sought to study the local expression and molecular regulation of the chemokines, regulated upon activation normal T cell expressed and secreted (RANTES) and macrophage inflammatory protein (MIP)-1α, in the murine diaphragm during sepsis. Constitutive expression levels of RANTES and MIP-1α, as well as their receptors, CCR1 and CCR5, were significantly higher in diaphragm than limb muscle. Sepsis was induced by acute lipopolysaccharide (LPS) delivery or subacutely by intratracheal administration of live Pseudomonas aeruginosa bacteria. Both sepsis models triggered a marked upregulation of RANTES and MIP-1α in the diaphragm. In vitro, stimulation of diaphragmatic muscle cells with LPS also led to RANTES upregulation. Inhibition of the NF-kB pathway using pharmacologic or dominant negative genetic approaches blocked the LPS-induced RANTES upregulation, while free radical scavengers had no effect. We conclude that sepsis leads to greatly increased expression of RANTES, MIP-1α and their cognate receptors in the diaphragm. Manipulation of the NF-kB pathway and other regulators of chemokine expression in the diaphragm could represent a novel method for mitigating the skeletal muscle inflammatory response associated with sepsis-induced diaphragmatic dysfunction.